2020
DOI: 10.35366/92889
|View full text |Cite
|
Sign up to set email alerts
|

Principales causas de automedicación en estudiantes del área de la salud

Abstract: www.conamed.gob.mx/revistaconamed.html www.medigraphic.org.mx Resumen Introducción: La OMS identificó a la automedicación como un componente del autocuidado en la salud; 80% de la población mexicana usa medicamentos por iniciativa propia sin indicación médica y sin receta. Objetivo: Identificar las principales causas de automedicación en estudiantes del área de la salud. Material y métodos: Se realizó un estudio transversal donde el universo del estudio fueron estudiantes del área de la salud de nivel licencia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 10 publications
0
3
0
4
Order By: Relevance
“…This is confirmed by several authors who demonstrated this problem with similar studies; Such is the case of (Castro et al 2022) in their study found a prevalence of (161.69%) of students from the Faculty of Health Sciences of the Nursing Career who self-medicated and there was a higher percentage in women (82%) as well as the age range was between 18 and 25 years (90%). (Alba et al 2020) in their study of students in the health area also found a prevalence of 88% corresponding to the female gender with 72% and their age ranged from 17 to 30 years with a percentage of 71 %. Likewise, I emphasize it (Morales, et al 2018) who in his study showed that 100% of his participants self-medicated, but he mentioned that there is a high prevalence in students who do it irresponsibly with a (90.7%) which is worrisome according to the aforementioned studies that are closely related to the data provided in this investigation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This is confirmed by several authors who demonstrated this problem with similar studies; Such is the case of (Castro et al 2022) in their study found a prevalence of (161.69%) of students from the Faculty of Health Sciences of the Nursing Career who self-medicated and there was a higher percentage in women (82%) as well as the age range was between 18 and 25 years (90%). (Alba et al 2020) in their study of students in the health area also found a prevalence of 88% corresponding to the female gender with 72% and their age ranged from 17 to 30 years with a percentage of 71 %. Likewise, I emphasize it (Morales, et al 2018) who in his study showed that 100% of his participants self-medicated, but he mentioned that there is a high prevalence in students who do it irresponsibly with a (90.7%) which is worrisome according to the aforementioned studies that are closely related to the data provided in this investigation.…”
Section: Discussionmentioning
confidence: 91%
“…There are various reasons for self-medication to occur, the main ones being economic resources, no health personnel service and lack of time, that is, the time to go to a doctor who diagnoses and offers treatment, which leads to 40% of adolescent students will choose to resort to self-medication, as mentioned by other authors such as (Alba, et al 2020) who affirms that 42.1% of adolescents will self-medicate due to lack of time, on 14, 4% for economy, that is, the same reasons. In his research (Castro, et al 2022) he mentions that there are different variables such as the distance from a health center 7%, not having resources available 1%, there is no service from the doctor 4% are the reasons for which 20% of students who do not have time to go to the doctor and decide to self-medicate, as stated (Ramírez, et al 2020) time is a predominant factor for self-medication to be carried out in 40% of the participants confirm it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No obstante, los puntos negativos son mayores dado que la automedicación podría ocultar y agravar el proceso de la patología, inducir a un diagnóstico y tratamiento incorrecto u ocasionar interacciones entre medicamentos que ocasionen reacciones adversas. (3) Según la Organización Mundial de la Salud (OMS), se alcanza hasta un 80 % de casos en los que se puede adquirir medicamentos, como antibióticos, sin receta en farmacias. (2) Además, en el mundo más de la mitad de los medicamentos son recetados o vendidos de forma inadecuada y un tercio de la población mundial no puede acceder a medicación básica.…”
Section: Introductionunclassified
“…La AI se presenta en distintos grupos etarios, entre ellos la población universitaria de acuerdo con el estudio de Alba-Leonel et al, (2022), los estudiantes de nivel superior, profesionales, son una población con mayor exposición a la adición a internet, junto a los adolescentes (Tur-Porcar et al, 2019). Romero-Rodríguez et al, (2021), mencionan que el uso inadecuado y excesivo del internet incide de mayor manera en universitarios que presentan síntomas de ansiedad, depresión y estrés afectando su bienestar personal.…”
Section: Introductionunclassified